Aspek Hukum Pidana Pada Tindakan Pencabulan Dibawah Umur Berdasarkan Undang-Undang No 35 Tahun 2014 - Jayanti, Yanuria; Krismiyarsi, Krismiyarsi (Jurnal JURISTIC, 2025)
Protection of children is an action to ensure, protect children and their rights in order to grow and develop optimally suit the dignity of humanity, approriate protection from violence and discrimination. Obscenity against a child is a criminal offense that attacks the honor of the child's decency. of the Child Protection Law states that anyone who has sex with a woman outside of marriage, even though it is known or properly should be assumed that she is not yet fifteen, or if her age is unclear, that it is not time to be married, threatened with criminal jail for a maximum of nine years. The purpose of writing this research is to explain the causes of sexual abuse of minors. This research method is carried out by using library research methods